2021
DOI: 10.48550/arxiv.2110.04902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthetic Data for Multi-Parameter Camera-Based Physiological Sensing

Abstract: Synthetic data is a powerful tool in training data hungry deep learning algorithms. However, to date, camerabased physiological sensing has not taken full advantage of these techniques. In this work, we leverage a high-fidelity synthetics pipeline for generating videos of faces with faithful blood flow and breathing patterns. We present systematic experiments showing how physiologically-grounded synthetic data can be used in training camera-based multi-parameter cardiopulmonary sensing. We provide empirical ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Synthetics pipelines have the advantage of allowing simulation of many different combinations of appearance types, contexts and physiological states example high heart rates or arrhythmia states for which it may be difficult to create to gather examples in a lab. Research has shown that greater and greater numbers of avatars in a synthetic training set can continue to boost performance up to a point [90]. However this is early work and there remains a "sim-to-real" gap in performance of these systems, models trained purely on synthetic data do not generalize perfectly to real videos.…”
Section: Synthetics and Data Augmentationmentioning
confidence: 99%
“…Synthetics pipelines have the advantage of allowing simulation of many different combinations of appearance types, contexts and physiological states example high heart rates or arrhythmia states for which it may be difficult to create to gather examples in a lab. Research has shown that greater and greater numbers of avatars in a synthetic training set can continue to boost performance up to a point [90]. However this is early work and there remains a "sim-to-real" gap in performance of these systems, models trained purely on synthetic data do not generalize perfectly to real videos.…”
Section: Synthetics and Data Augmentationmentioning
confidence: 99%